STAGECRAFT:ANANALYSISOFSCENO GRAPHIC NETWORK IN THE THEMATIC CONCERNS IN MAHESHDATTANI’SPLAYS - RAJESWARIBONAM (International Journal of Psychosocial Rehabilitation, 2021)
Drama is a powerful medium of communication to exhibit and explore the human world in various dimensions. It is not simply constructed with a plot and characters. Intelligent stagecraft and dramatic techniques of a playwright convey many things beyond her/his words and actions. MaheshDattani is a brilliant dramatist and excellent stage crafter who makes his audience react to the elements onstage and script, and draws spectators and readers to comprehend the matter of life even in some lifeless properties on stage. Unless understanding his stagecraft and techniques, no one could comprehend his plays in a right sense. His stage direction, movement, settings, and dramatics are what matter to understand his texts, especially his plays, Tara and Dance like a Man.